2014
DOI: 10.1016/j.pain.2013.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity to physical activity among individuals with knee osteoarthritis: Relation to pain outcomes, psychological factors, and responses to quantitative sensory testing

Abstract: Recent findings suggest that certain individuals with musculoskeletal pain conditions have increased sensitivity to physical activity (SPA) and respond to activities of stable intensity with increasingly severe pain. This study aimed to determine the degree to which individuals with knee osteoarthritis (OA) show heightened SPA in response to a standardized walking task and whether SPA cross-sectionally predicts psychological factors, responses to quantitative sensory testing (QST), and different OA-related out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
129
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(152 citation statements)
references
References 88 publications
18
129
4
1
Order By: Relevance
“…21 Interestingly, previous studies have also reported a relationship between measures of pain augmentation (such as TSP and PAS), and indices of negative affect, anxiety, and fear of pain. 25,63,66,80 In the present study, we similarly found a significantly higher report of pain-related catastrophizing as well as PAS among subjects with FM, whether measured as a stable trait with the PCS, or measured “situationally” in reference to experimental pain stimulation (SPCS). However, within the FM subject cohort, there was not a significant correlation between PAS and measures of catastrophizing (Table 3).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…21 Interestingly, previous studies have also reported a relationship between measures of pain augmentation (such as TSP and PAS), and indices of negative affect, anxiety, and fear of pain. 25,63,66,80 In the present study, we similarly found a significantly higher report of pain-related catastrophizing as well as PAS among subjects with FM, whether measured as a stable trait with the PCS, or measured “situationally” in reference to experimental pain stimulation (SPCS). However, within the FM subject cohort, there was not a significant correlation between PAS and measures of catastrophizing (Table 3).…”
Section: Discussionsupporting
confidence: 78%
“…Whereas PAS have been studied by several groups psychophysically, their associated brain activity has not been investigated. Furthermore, although negative cognitive and affective factors such as catastrophizing, anxiety, and fear are known to contribute to pain-facilitatory processes, 24,25,63,66,80 it is unclear from previous work how negative affect relates to the experience of PAS.…”
mentioning
confidence: 99%
“…Of eleven studies [14][15][16][17][18][19][20][21][22][23][24], six at least showed a significant relationship between depression and pain, but these findings corresponded to evidence level IV because they were confirmed by cross-sectional studies; the results of the two cohort studies were not consistent. Pain catastrophizing had been measured by ten studies [14,15,19,20,23,[25][26][27][28][29] in our review and was shown to be related with pain worsening in six cross-sectional studies as evidence level IV and in one prospective cohort study as evidence level II. Self-efficacy was significantly related to pain worsening in four studies [16,25,27,30], and one study suggesting this finding …”
Section: Assessment Of the Risk Of Biasmentioning
confidence: 80%
“…The data presented by Neogi et al support translational relevance to human OA of these findings in RA and in preclinical models. Central sensitization might also be driven by genetic constitution or comorbid fibromyalgia (11) and by concurrent psychological factors such as catastrophizing (12) and distress (13). The prospective study by Neogi and colleagues indicates a likely contribution of synovitis to progressive widespread sensitization, determined by quantitative sensory testing, that is largely independent of these other factors.…”
Section: David a Walshmentioning
confidence: 99%